2010
DOI: 10.3155/1047-3289.60.8.907
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a Predictive Emissions Monitoring System Applied to Taipower’s Nanpu and Hsinta Power Plants

Abstract: The Hsinta and Nanpu Power Stations are located in southern Taiwan. The Hsinta Power Station consists of five combined-cycle gas turbines (CCGT), whereas the Nanpu Power Station consists of four. A project was undertaken to develop and deploy a predictive emissions monitoring system (PEMS) on CCGT unit 3 of Hsinta Power Station (HT-3) and CCGT unit 1 of Nanpu Power Station (NP-1) with the long-term goal of developing a universal model for this kind of power plant. After the first-year PEMS project at the Hsint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In 2010, Chien et al applied the same model to the same size and type cogeneration unit but at a different power station, Nanpo station, and concluded that the statistical model could not be transferred from one piece of equipment to another due to differences in equipment condition, operating model, maintenance and other parameters. [24].…”
Section: Pems Researchmentioning
confidence: 99%
“…In 2010, Chien et al applied the same model to the same size and type cogeneration unit but at a different power station, Nanpo station, and concluded that the statistical model could not be transferred from one piece of equipment to another due to differences in equipment condition, operating model, maintenance and other parameters. [24].…”
Section: Pems Researchmentioning
confidence: 99%
“…Computer-based predictive emission monitoring systems (PEMSs) have become attractive because of their low capital and operating costs, and low maintenance (Chien et al, 2010;Cooper and Andreasson, 1999;Harnevie et al, 1996). PEMSs can not only be used to replace existing aging CEMSs but also can be installed on small combustion sources, for which CEMSs are normally cost-prohibitive for emission monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…At present, almost all atmospheric environmental monitoring data is used to prepare environmental reports such as daily newspapers and annual reports (Arsie et al, 2010;Marino et al, 2017) while the value of data needs to be further explored (Li et al, 2014). For example, through historical monitoring data, the future trend of atmospheric environmental quality can be predicted so as to better guide people's production activities (Chien et al, 2005(Chien et al, , 2010. Meanwhile, it provides relevant scientific evidence for government decision-making and management departments in the formulation of systems concerning this area (Chien et al, 2003).…”
Section: Introductionmentioning
confidence: 99%